2022
DOI: 10.17707/agricultforest.68.1.09
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF EXTRACTION SOLVENT ON BIOACTIVE COMPOUNDS AND ANTIOXIDANT ACTIVITY OF Cichorium intybus L. GROWN IN KOSOVO

Abstract: The aim of this study was the investigation of the total phenolic content, flavonoid, and the assessment of the antioxidant potential of Cichorium intybus L. flowers grown in the Kosovo region. The flowers of Cichorium intybus L. were collected, dried, and extracted with solvents with different polarities (water, EtOH, MeOH, EtOAc, and acetone), using the extraction method. The total phenolic and flavonoid contents were analyzed by using Folin-Ciocalteu's and AlCl3 reagents, respectively. The antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Nevertheless, TPCs (mg GAE/100 g DW) were lowest in the de-ionized water extract (66.67). Comparing the phenolic contents of current study to earlier data reveals differences [49].…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…Nevertheless, TPCs (mg GAE/100 g DW) were lowest in the de-ionized water extract (66.67). Comparing the phenolic contents of current study to earlier data reveals differences [49].…”
Section: Resultscontrasting
confidence: 41%
“…He con rmed that C. intybus has a very high avonoid content. The variations in avonoid levels observed in this study might potentially be attributed to variations in plant parts, extraction solvent system, and geographic variability [49]. Figure 6 shows the graphical comparison of Total avonoid contents (mg CE/g DW) C. intybus leaves varying solvents system.…”
Section: Resultsmentioning
confidence: 89%
“…Total phenolic contents of the extract of strawberry fruits were assessed by Folin-Ciocalteu reagent using the method previously reported by Singleton et al (1999) with slight modification, with the assistance of Folin-Ciocalteu reagent by Koraqi and Lluga-Rizani (2022). Briefly, 1 mL of each fruit extract diluted 1:20 with five different concentrations (12.5, 25, 50, 100, and 200 mg/mL) of each extract (in water, methanol, ethanol, acetonitrile, and acetone) was mixed with 1 mL distilled water and 500 μL Folin-Ciocalteu reagent and stirred for 1 min.…”
Section: Total Polyphenol Content Determinationmentioning
confidence: 99%
“…Total phenolics content (TPC) was determined by Folin Ciocalteu Reagent spectrophotometrically at 765 nm using the method of Singleton et al (1999), 17 with some modifications reported by Koraqi and Lluga-Rizani (2022) 18 . The results are presented as mg gallic acid (mg GAE/g DW) equivalent per gram Rosa canina L. fruits sample.…”
Section: Determination Of Bioactive Properties and Antioxidant Activi...mentioning
confidence: 99%